A review on the operational parameters and degradation kinetics used in anaerobic co-digestion of tannery residues - Shilpy Rani Basak; Samin Azhan Chowdhury; Rafiuzzaman Khan; Ahmad Hasan Nury; Md. Jahir Bin Alam; Md. Imran Kabir (Waste Management Bulletin)
Tannery residues possess the potential to produce biogas through anaerobic co-digestion processes. Research related to anaerobic co-digestion of food wastes and easily biodegradable wastes is ongoing and a vast advancement has been observed already to reclaim biogas as recycled energy. However, a review on the co-digestion of tannery residues and their potentiality to produce recycled energy has been initiated very limitedly. As these residues are more persistent compared to the biodegradable ones, their conversion to a simpler and safer form is highly required. To fill in this gap, an approach to review the co-digestion of tannery residues and its potential degradation kinetics has been initiated here so that the prime co-digestion- and kinetic- parameters are evaluated. Moreover, four generic equations with 45 parameters (variable and constant) have been developed based on the existing literature to explain the bacterial growth with substrate- and product- inhibition as well as substrate degradation. This review outcome will lead to the biochemical modelling of the degradation of tannery residues for various co-digestion elements. It will lead the modelers to find not only the potential parameters to be considered during co-digestion but also the effective initiations of related experiments.